2017
DOI: 10.4037/ajcc2017916
|View full text |Cite
|
Sign up to set email alerts
|

Stress and Coping of Critical Care Nurses After Unsuccessful Cardiopulmonary Resuscitation

Abstract: Background Participation by a critical care nurse in an unsuccessful resuscitation can create a unique heightened level of psychological stress referred to as postcode stress, activation of coping behaviors, and symptoms of posttraumatic stress disorder (PTSD). Objectives To explore the relationships among postcode stress, coping behaviors, and PTSD symptom severity in critical care nurses after experiencing unsuccessful cardiopulmonary resuscitations and to see whether institutional support attenuates these r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
55
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 39 publications
6
55
1
2
Order By: Relevance
“…A number of studies has used Brief-COPE to examine nurses coping strategies (Alharbi & Alshehry, 2019;Fathi & Simamora, 2019;McMeekin, Hickman Jr, Douglas, & Kelley, 2017), however, in the absence of validation study, the results reported may be problematic and disputed. In particular, the CFA models using structure from previous studies did not achieve good t, observed high cross-loadings, and Cronbach's alpha of individual subscales were inadequate (although most were above 0.5),…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies has used Brief-COPE to examine nurses coping strategies (Alharbi & Alshehry, 2019;Fathi & Simamora, 2019;McMeekin, Hickman Jr, Douglas, & Kelley, 2017), however, in the absence of validation study, the results reported may be problematic and disputed. In particular, the CFA models using structure from previous studies did not achieve good t, observed high cross-loadings, and Cronbach's alpha of individual subscales were inadequate (although most were above 0.5),…”
Section: Discussionmentioning
confidence: 99%
“…Coping strategies are an important stabilizing factor in managing the challenging situations that nurses encounter on a daily basis in the work environment. Several international studies have addressed selection of coping strategies in nurses (McMeekin et al, 2017;Pašková, 2018;Pašková & Rapčíková, 2020;Ramezanli et al, 2015;Ribeiro et al, 2015;Sondhi et al, 2019;Sováriová Soósová & Varadyová, 2012), the findings of which suggest that nurses use several varieties of coping strategies. Lazarus & Folkman (1984) mention three basic methods of coping: coping involving the resolution of a given problem; coping involving mitigation of negative experiences (to improve emotional balance rather than to resolve the problem itselfa symptomatic reaction, which can help the individual for a limited time), coping involving avoidancethe individual tries not to face the problem, preferring to forget about it and escape it.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, identifying coping resources that may hinder stress management or better enable students to cope with their work environment and reduce stress is the place of key. Exiting evidence have showed that when negative events happened in clinical practice (e.g., medical errors or did clinical task not achieving the expectation, or patients died), students often use maladaptive coping strategies such as self-blame, blame of impersonal forces or the "system, " and blame of others (Collins et al, 2009), which in turn add their psychological stress, even lead to mental illness (Al-Dubai et al, 2011;McMeekin et al, 2017;Ludwig et al, 2019).…”
Section: Introductionmentioning
confidence: 99%